Thermal Conductivity of Liquid Lead for the Fast Nuclear Reactor Coolant, Calculated by the Green-Kubo Method Using Molecular Dynamics Simulation - Artoto Arkundato; Ratna Dewi Syarifah; Lutfi Rohman; Wenny Maulina; Widiasih (Postgraduate, University of Mataram, 2023)
Comprehensive information about nuclear reactor coolant materials for application in heat-transfer systems is very important. One important physical property that needs to be known is the thermal conductivity. The goal of this work is to predict the thermal conductivity value of the liquid lead, which is one of the important candidates for cooling materials for Gen-IV fast nuclear reactor designs. The thermal conductivity of liquid lead in this study was predicted using the Green-Kubo scheme and the molecular dynamics (MD) computational method to collect the simulation data. The MD simulation was done in the NVT ensemble, using the Lennard-Jones interaction potential. We observe the thermal conductivity of the liquid lead can be studied based on the diffusion physical process. The thermal conductivity of the liquid lead obtained from this research is Î» = 0.0113T + 8.8539 [W/mK]. As a conclusion, this result is very suitable, compared with the available experimental data, then the Green-Kubo method can be used to calculate the thermal conductivity of liquid metal as lead.